Vitamin C supplementation in patients with hypothyroidism requiring high-dose levothyroxine: a proof-of-concept pilot study - Agha, Adnan; Afandi, Bachar; Yasin, Javed; Sharma, Charu; Alshaer, Mohammad Hamdan; Alshamsi, Mouza Ali Saif; Yaaqeib, Dana Ebraheim; Alblooshi, Bayena Khamis Eshaq; AlKaabi, Juma (Frontiers in Endocrinology, 2025)
BackgroundVitamin C supplementation may enhance the absorption of levothyroxine in patients with hypothyroidism. This proof-of-concept pilot study aimed to assess the frequency of vitamin C insufficiency and evaluate the feasibility and potential therapeutic signal of vitamin C supplementation in patients requiring high-dose levothyroxine.MethodsThis two-phase study initially assessed vitamin C levels in 26 hypothyroid patients and 91 healthy controls. In phase two, a double-blind, randomized, placebo-controlled trial was conducted. Twelve patients were randomized, and 11 completed the study. Participants received either 1g daily vitamin C (n=6) or a near-matched pH placebo (n=5) for 16 weeks. Primary outcomes were changes in the Zulewski clinical score and thyroid-stimulating hormone (TSH) levels.ResultsVitamin C insufficiency was more frequent in hypothyroid patients (19.2%) versus controls (7.7%), though the difference in mean levels was not statistically significant (59.33 ± 24.62 µmol/L vs 73.12 ± 14.03 μmol/L in controls; p=0.21). In the RCT, the vitamin C group showed greater changes in Zulewski score (mean reduction 5.00 vs 1.40 points; difference 3.60, 95% CI: 1.88 to 5.32) and TSH levels (mean reduction 4.08 vs 2.35 mU/L; difference 1.73, 95% CI: -2.14 to 5.60) compared to placebo. However, the groups had significant baseline imbalances, notably in BMI (26.6 vs 43.4 kg/m²). After ANCOVA adjustment for baseline values, the between-group difference remained statistically significant for the Zulewski score (adjusted p=0.004) and marginally significant TSH (adjusted p=0.043). Primary biochemical outcome in this study was TSH rather than direct thyroid hormone measurement, as TSH represents the most sensitive biomarker for thyroid hormone adequacy in primary hypothyroidism and serves as the established therapeutic target in clinical guidelines.ConclusionsThis proof-of-concept study demonstrates the feasibility of studying vitamin C supplementation in patients on high-dose levothyroxine and detects a therapeutic signal, particularly in clinical symptoms. However, the findings are limited by the very small sample size and severe baseline imbalances, precluding any conclusions on efficacy. These preliminary data justify the need for larger, well-controlled trials with stratified randomization to determine if this intervention translates into a clinically meaningful effect.Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT05733078, identifier NCT05733078.